2013
DOI: 10.1007/s12010-013-0471-0
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of an Ethanol-Tolerant β-Glucosidase from Sporidiobolus pararoseus and Its Potential for Hydrolysis of Wine Aroma Precursors

Abstract: An extracellular ethanol-tolerant β-glucosidase from Sporidiobolus pararoseus was purified to homogeneity and characterized, and its potential use for the enhancement of wine aroma was investigated. The crude enzymatic extract was purified in four steps (concentration, dialysis, ultrafiltration, and chromatography) with a yield of around 40 % for total activity. The purified enzyme (designated Sp-βgl-P) showed a specific activity of approximately 20.0 U/mg, an estimated molecular mass of 63 kDa after sodium do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…pararoseus is a potential candidate organism for the study of the regulation of the carotenoids biosynthetic pathway, due to their production of the primary carotenoid β-carotene and torulene as well as the secondary carotenoids γ-carotene and torularhodin (Mannazzu et al, 2015;Mata-Gomez et al, 2014). However, despite a considerable number of reports on carotenoids bioproduction by S. pararoseus, little is known about the presence of carotenogenic genes, nor the molecular mechanisms underlying carotenoid biosynthesis in S. pararoseus (Baffi et al, 2013;Cabral et al, 2011;Han et al, 2012;Shi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…pararoseus is a potential candidate organism for the study of the regulation of the carotenoids biosynthetic pathway, due to their production of the primary carotenoid β-carotene and torulene as well as the secondary carotenoids γ-carotene and torularhodin (Mannazzu et al, 2015;Mata-Gomez et al, 2014). However, despite a considerable number of reports on carotenoids bioproduction by S. pararoseus, little is known about the presence of carotenogenic genes, nor the molecular mechanisms underlying carotenoid biosynthesis in S. pararoseus (Baffi et al, 2013;Cabral et al, 2011;Han et al, 2012;Shi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many researchers have searched for novel enzymes tolerant to glucose or have attempted to learn more about the mechanism that leads to tolerance to implement this feature in other enzymes through engineering [2,26–29]. Moreover, a demand exists for new β-glucosidases with tolerance to some alcohols present in the biofuel and beverage industry processes [12,17,63]. …”
Section: Resultsmentioning
confidence: 99%
“…This process is largely applied in wine and juice production and involves the liberation of flavouring compounds from certain precursors, such as glycoside monoterpenes (linalool, geraniol, and nerol) [12,17,18]. However, the application of ß-glucosidases could be greatly extended by using many enzyme activities to modify sugars in food products, such as an enzyme’s lactase activity.…”
Section: Introductionmentioning
confidence: 99%
“…The optimal temperature of the purified β‐glucosidase is 60 °C, which is similar to those of other known ones from some microorganisms, such as Fusarium oxysporum (60 °C) , Aspergillus fumigates (60 °C) , the protoplast fusant of Aspergillus oryzae and A. niger (65 °C) , and Colletotrichum graminicola (65 °C) . Compared to many acidic β‐glucosidases from Sporidiobolus pararoseus (pH 4.0) , A. niger (pH 4.0) , Penicillium aculeatum (pH 4.5) , Oenococcus oeni (pH 5.0–5.5) , and Endophytic fungi (pH 5.0 and 6.0) , the β‐glucosidase from Bacillus sp. ZJ1308 shows an optimal activity at pH 7.0, indicating that it may be neutral.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that several β‐glucosidases have a high activity for the hydrolysis of daidzin , genistin , stevioside , oleuropein , and echinacoside . β‐Glucosidase has been widely used for the improvement of wine aroma . Some studies have pointed out that the activity of β‐glucosidase may become a good candidate for the propolis‐freshness index .…”
Section: Introductionmentioning
confidence: 99%